Continuous renal replacement therapy attenuates polymorphonuclear myeloid-derived suppressor cell expansion in pediatric severe sepsis - Feng, Shuyun; Cui, Yun; Zhou, Yiping; Shao, Lujing; Miao, Huijie; Dou, Jiaying; Liu, Tiantian; Wang, Chunxia; Zhang, Yucai (Frontiers in Immunology, 2022)
Background: Myeloid-derived suppressor cells (MDSCs) expansion is an important mechanism underlying immunosuppression during sepsis. Though continuous renal replacement therapy (CRRT) may attenuate hyperinflammatory response in sepsis, its role in regulating MDSCs is unknown. The aim of this study was to assess the potential role of CRRT involved in sepsis-induced MDSCs expansion in pediatric sepsis. Method: The proportion of polymorphonuclear MDSCs (PMN-MDSCs) was detected before CRRT (pre-CRRT), at 24 hours after CRRT (CRRT 1st day) and at 7 days after CRRT (CRRT 7th day). The correlation analyses were performed to elucidate the relationship of MDSCs with clinical indexes in sepsis. Results: Totally 22 pediatric patients with sepsis were enrolled [median age 44 (IQR15, 83) months]. PMN-MDSCs were expanded in pediatric sepsis compared with healthy controls (4.30 % vs. 0.37%, P=0.04). The proportion of PMN-MDSCs showed a decreased tendency at CRRT 7th day compared with that at CRRT 1st day in survivors (2.29% vs.5.32%, P = 0.088). PMN-MDSCs between survivors and non-survivors was observed pre- CRRT (4.51% vs. 3.33%, P = 0.745). The levels of interleukin 6 (IL-6) was decreased at CRRT 7th day compared with CRRT 1st day in survivors. In the subgroups of patients with significantly decreased IL-6 levels after CRRT, the proportion of PMN-MDSCs at CRRT 7th day were also significantly decreased compared with that at CRRT 1st day (2.21% vs. 6.67%, P = 0.026). Conclusion: The proportion of PMN-MDSCs was down-regulated after CRRT 7th day in survivor patients with sepsis. The decline PMN-MDSCs expansion may relate to decreased IL-6 level.